HARNESSING SOCIAL MEDIA FOR ONLINE LEARNING IN HIGHER EDUCATION PROGRAM - Jamridafrizal Jamridafrizal (Saintifika Islamica, 2017)
Social media tools are harnessed to communicate and increase engagement of users which would have strong and positive effects. Many Lecturers and Students in colleges have used social media for sharing information with their students, but this media has not been used for the purpose of formal learning. It seems to throw off the huge potential already provided by social media to make it easier for everyone to deliver messages for educational purposes. This research is based on library research. This paper offers a thought on how social media can be laveraged with the design of learning environment in such a way to deliver instruction in higer education, so that lecturers and students can interact whenever and wherever they are without being disturbed by their physical absence in the classroom. Keyword: Social Media, Higher Education, Online Collaborative Learning,Web 2.0